Hajdúböszörmény településmorfológiai képződményeinek változásai a XIX–XX. században - Tóth, Antal (Tér és Társadalom, 1996)
The present study examines those seftlement morphological formations (base map, road etwork, arrangement of the sites, way of building up), in which the life of a town takes lace. It attempts to fill a gap in the field, as the morphological aspects of urbanisation still ave not been explored to the necessary depth. In my study I mainly analyse the evelopment history of the base map and image of the settlement. The choice of the seftlement is explained by the settlement geographical features of Hajdúböszörmény. The town still bears its history in its appearance: Its most precious onument are the town itself and its morphology. In the second half of the survey I processed the findings of a comparative morphological examination. The analysis of the former morphological picture and the comparisons are ade possible by Tibor Mendöl’s research in settlement geography, carried out 60 years ago. Primarily I examined the evolution of the shape, location, structure and size of the core of the town, by exploring morphological forms and ways of construction, putting their spatial arrangement onto a map.